Report of two cases of missed uterus rupture after normal vaginal delivery without previous scar - Kosar Deldar; Seyed Saleh Seyedein; Marzieh Lotfalizadeh; Mansoureh Mohammadnezhad (Mashhad University of Medical Sciences, 2019)
Introduction: Uterus rupture during pregnancy is a fatal complication or is associated with severe maternal and fetal complications. In some cases, due to the lack of timely diagnosis of uterus rupture, the patient will refer with bad state that in the case of early diagnosis, faster intervention can be performed Case Report: In this report, two cases of uterine rupture were introduced; the first case of uterine rupture occurred following motor trauma and fetal death and vaginal delivery, and the patient referred with metrite symptom and omentom herniation to ruptured uterus, and the second case, rupture of the uterus was due to pressure on the fundus during delivery in the patient without uterine scar, which referred as delayed due to the intestinal herniation to the uterus with acute abdomen obstructive symptoms. Conclusion: It is recommended that in patients with abdominal trauma, especially with fetal death, and in patients who have infant infected with blood, after delivery, despite the completeness of the placenta and absence of bleeding, an intrauterine assessment in terms of uterus rupture be performed with hand, and faster intervention be done in the case of diagnosing rupture uterus.